2015
DOI: 10.1111/prd.12082
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar socket healing: what can we learn?

Abstract: Tooth extraction induces a series of complex and integrated local changes within the investing hard and soft tissues. These local alterations arise in order to close the socket wound and to restore tissue homeostasis, and are referred to as '"socket healing". The aims of the present report were twofold: first, to describe the socket-healing process; and, second, to discuss what can be learned from the temporal sequence of healing events, in order to improve treatment outcomes. The socket-healing process may be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
377
0
34

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 357 publications
(418 citation statements)
references
References 66 publications
7
377
0
34
Order By: Relevance
“…In the review by Araújo et al. (2015), he postulated that, following tooth extraction, “… (i) up to 50% reduction in the original ridge width will occur; (ii) the amount of bone resorption will be greater at the buccal aspect than at its lingual/palatal counterpart; and (iii) a larger amount of alveolar bone reduction will take place in the molar regions.” In this review of clinical studies with various biomaterials, it was concluded that ridge contraction following tooth extraction can be minimized with socket grafts and/or the use of mechanical barriers. While grafts alone might be sufficient for space‐maintaining sockets, others have found grafts plus membranes to be advantageous, particularly for limited space‐maintaining defects like the dehiscence defects studied herein (Kim et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the review by Araújo et al. (2015), he postulated that, following tooth extraction, “… (i) up to 50% reduction in the original ridge width will occur; (ii) the amount of bone resorption will be greater at the buccal aspect than at its lingual/palatal counterpart; and (iii) a larger amount of alveolar bone reduction will take place in the molar regions.” In this review of clinical studies with various biomaterials, it was concluded that ridge contraction following tooth extraction can be minimized with socket grafts and/or the use of mechanical barriers. While grafts alone might be sufficient for space‐maintaining sockets, others have found grafts plus membranes to be advantageous, particularly for limited space‐maintaining defects like the dehiscence defects studied herein (Kim et al.…”
Section: Discussionmentioning
confidence: 99%
“…1985, Wood & Mealey 2012), while others have employed mineralized, more rigid, minimally resorbing and reportedly osteoconductive grafts (Berglundh & Lindhe 1997, Araújo et al. 2015). …”
mentioning
confidence: 99%
“…1,2,3,4 In posterior regions of the upper jaw, maxillary sinus approximation may be present and such event, in combination with bone loss, can difficult implant installation in these sites.…”
mentioning
confidence: 99%
“…Intraoral clinical examination, cone beam computed tomography (CBCT) and facial analysis found the patient to have missing teeth (13,14,15,16), esthetic problems with the reminiscent teeth (12,11,21,22,23,24,25,26,27,28), root resorption of the anterior teeth, malpositioned teeth and Class III occlusion (Figure 1 & 2). The risks and benefits of many alternative of dental treatment were evaluated and chosen option recommended to correct the functional and esthetic patient complaints was the extraction of the all the remaining teeth aiming the placement of dental implants and a restoration with a fixed prosthesis.…”
Section: Case Presentationmentioning
confidence: 99%
“…The results obtained did not indicate the most indicated surgical approach or biomaterial, although with the use of membrane barriers, surgery with flap and total closure of the flap with first intention healing showed better results. Araújo et al [15] made a systematic review on alveolar bone healing and concluded that there are four main principles that should be taken into consideration in the alveolar bone healing process. First, the alveolus, in the anterior region of the maxilla, is characterized by a thin buccal bone wall.…”
Section: The Type Of Evaluation Usedmentioning
confidence: 99%